Interaction Of Communities With Forest In The Utilization Of Non-Timber Forest Product In Segati Village Sub-District Langgam District Pelalawan Riau Province - Miranti Putri R.G; Defri Yoza; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Interaction between people and forests have lasted long enough for forests provide benefits to society such as non-timber forest products (NTFPs). Behavior between communities and forests in the utilization of NTFPs is a form of interaction that occurs between people and forests. Village which is the object of this research is segati village in order to determine the shape and pattern of interaction communitieswithforestin the utilization of NTFPs and to determine the location of the distribution of the use of NTFPs in the village Segati. This study was conducted for 6 months starting in January 2013 to June 2013. Data collected in this study is by interview and observation. The sampling method was performed using purpossive sampling method with the criteria segati rural communities, which interact directly with the forest and the companies related with the utilization of the data is performed NTFPs segati villagers. The results of this study indicate a form of interaction that occurred in the community in the utilization of NTFPs that positive interactions and negative interactions with regular and seasonal patterns of interaction. For the location of the distribution of the utilization of NTFPs is done in two locations: in the concession area and outside of concession area. Keywords: Interaction, Forest Community, Utilization, Non-Timber Forest Product